Transformasi Digital dan Pertumbuhan UMKM: Analisis Dampak Teknologi pada Kinerja Usaha Kecil dan Menengah di Indonesia - Pratamansyah, Surya Ryan (Indonesian Journal Publisher, 2024)
This study examines the impact of digital transformation on the growth of Small and Medium Enterprises (SMEs) in Indonesia, focusing on the impact of technology on SME performance. A quantitative approach with a survey method was employed, involving 100 SMEs across various sectors in Indonesia. Data was collected through questionnaires measuring variables such as the use of e-commerce, social media, and management information systems as indicators of digital transformation, and increased revenue, efficiency, and market reach as indicators of SME performance. Multiple linear regression analysis revealed that digital transformation has a positive and significant impact on SME performance. The findings demonstrate that every one-unit increase in the digital transformation variable results in a 1.5-unit increase in SME performance. Furthermore, the study identified factors influencing the adoption of technology by SMEs, such as internet access, digital literacy levels, and government support. The analysis indicates that high internet access and digital literacy, along with strong government support, are crucial factors in increasing technology adoption and maximizing the benefits of digital transformation for SMEs. The study recommends strategies to encourage digital technology adoption by SMEs in Indonesia, including improving digital infrastructure, providing training and mentoring programs, and offering incentive schemes for digitally transforming SMEs.